The effect of systemic administration of G-CSF on a full-thickness cartilage defect in a rabbit model MSC proliferation as presumed mechanism: G-CSF for cartilage repair. Issue 3 (March 2017) - Sasaki, T.; Akagi, R.; Akatsu, Y.; Fukawa, T.; Hoshi, H.; Yamamoto, Y.; Enomoto, T.; Sato, Y.; Nakagawa, R.; Takahashi, K.; Yamaguchi, S.; Sasho, T.
Abstract : Objectives: The aim of this study was to investigate the effect of granulocyte-colony stimulating factor (G-CSF) on mesenchymal stem cell (MSC) proliferation in vitro and to determine whether pre-microfracture systemic administration of G-CSF (a bone marrow stimulant) could improve the quality of repaired tissue of a full-thickness cartilage defect in a rabbit model. Methods: MSCs from rabbits were cultured in a control medium and medium with G-CSF (low-dose: 4 μg, high-dose: 40 μg). At one, three, and five days after culturing, cells were counted. Differential potential of cultured cells were examined by stimulating them with a osteogenic, adipogenic and chondrogenic medium. A total of 30 rabbits were divided into three groups. The low-dose group (n = 10) received 10 μg/kg of G-CSF daily, the high-dose group (n = 10) received 50 μg/kg daily by subcutaneous injection for three days prior to creating cartilage defects. The control group (n = 10) was administered saline for three days. At 48 hours after the first injection, a 5.2 mm diameter cylindrical osteochondral defect was created in the femoral trochlea. At four and 12 weeks post-operatively, repaired tissue was evaluated macroscopically and microscopically. Results: The cell count in the low-dose G-CSF medium was significantly higher than that in the control medium. The differentiation potential of MSCs was preserved after culturing them with G-CSF. Macroscopically, defects were filled and surfaces were smoother in the G-CSF groups than in the control group at four weeks. At 12 weeks, the quality of repaired cartilage improved further, and defects were almost completely filled in all groups. Microscopically, at four weeks, defects were partially filled with hyaline-like cartilage in the G-CSF groups. At 12 weeks, defects were repaired with hyaline-like cartilage in all groups. Conclusions: G-CSF promoted proliferation of MSCs in vitro . The systemic administration of G-CSF promoted the repair of damaged cartilage possibly through increasing the number of MSCs in a rabbit model. Cite this article : T. Sasaki, R. Akagi, Y. Akatsu, T. Fukawa, H. Hoshi, Y. Yamamoto, T. Enomoto, Y. Sato, R. Nakagawa, K. Takahashi, S. Yamaguchi, T. Sasho. The effect of systemic administration of G-CSF on a full-thickness cartilage defect in a rabbit model MSC proliferation as presumed mechanism: G-CSF for cartilage repair. Bone Joint Res 2017;6:123–131. DOI: 10.1302/2046-3758.63.BJR-2016-0083.